Quantitative assessment of paratonia and its neuropsychological correlates in a geriatric population of patients with cognitive impairment. Issue 1 (January 2019) - Marinelli, L.; Puce, L.; Monacelli, F.; Trompetto, C.
Abstract : Paratonia is related to cognitive impairment, even though its prevalence in elderly subjects and its correlation with neuropsychological parameters is lacking. The aim of our study is to assess the prevalence of facilitatory and oppositional paratonia, evaluated with a quantitative electromyographic approach, and better understand its neuropsychological correlates. We recruited 16 patients with cognitive impairment and 10 controls without cognitive impairment. All subjects underwent a thorough neuropsychological and geriatric evaluation. Paratonia was measured with clinical scales and with surface electromyography. The amplitude of bursts from biceps and triceps brachii was assessed during 15 metronome-synchronized passive movements, performed at two velocities, in a continuous or discontinuous way, with the non-dominant upper limb. Paratonic bursts amplitude increased during movement repetition, mostly when movements were performed continuously. Facilitatory paratonia prevailed over oppositional; the normalized burst amplitude was higher on biceps compared to triceps brachii. Subjects with lower scores at Mini Mental Status Examination or Frontal Assessment Battery showed higher paratonia. Paratonia could be recorded also in control subjects. Paratonia prevails in subjects with severe cognitive impairment but can be also detected in age-matched controls. Paratonia increases during passive movement repetition and prevails in elbow flexors.